Energy Diversification Indonesian Railways - Sovian Aritonang; Imam Supriyadi; Betty Silalahi (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2016)
This study aims to find alternative energy in substitution high speed diesel (HSD) in the railway by measuring the economic, supply chain, and liquefied natural gas (LNG) optimization especially in Java. The economic analysis using the feasibility of investment method in LNG locomotive, supply chain analysis to simulate infrastructure of transportation and distribution LNG to identify internal and external factors affecting. The economic analysis result showed fuel saving costs up to 36%, the NPV is positive, and the IRR higher than the discount rate so the investment is feasible to held that will bring benefits for country’s revenues from using dual fuel in LNG locomotive. Supply chain analysis provide two simulation models of LNG distribution for railway that suitable to be applied in Java Island, the source of LNG coming from outside Java Island using existing LNG plant and the source of LNG coming from inside Java Island using mini LNG plant.